Adjuvant therapy use among Appalachian breast cancer survivors. Issue 26 (July 2015) - Tan, Xi; Marshall, Vincent D.; Anderson, Roger T.; Donohoe, Joseph; Camacho, Fabian; Balkrishnan, Rajesh
Abstract : Abstract: There is a paucity of literature systemically examining the effects of access to cancer care resources on adjuvant endocrine therapy (AET) use behaviors, especially in underserved regions such as the Appalachian region in the United States, where gaps in healthcare access are well documented. The objectives of this study were to explore AET adherence and persistence in Appalachia, delineate the effects of access to care cancer on adherence/persistence, and evaluate the influences of adherence and persistence on overall survival. A retrospective cohort study from 2006 to 2008 was conducted among female breast cancer survivors living in the Appalachian counties of 4 states (PA, OH, KY, and NC). We linked cancer registries to Medicare claims data and included patients with invasive, nonmetastatic, hormone-receptor-positive breast cancer who received guideline-recommended AET. Medication adherence was defined as corresponding to a Medication Possession Ratio (MPR) ≥0.8 and logistic regression was utilized to assess predictors of adherence. Medication nonpersistence was defined as the discontinuation of drugs after exceeding a 60-day medication gap, and multivariate adjusted estimates of nonpersistence were obtained using the Cox proportional hazards (PH) model. About 31% of the total 428 patients were not adherent to AET, and 30% were not persistent over an average follow-up period of 421 days. Tamoxifen, relative to aromatase inhibitors, was associated with higher odds of adherence (odds ratio = 2.82, P  < 0.001) and a lower risk of nonpersistence (hazard ratio = 0.40, P  < 0.001). Drug-related side effects like pain may be an important factor leading to nonadherence and early discontinuation. In addition, aromatase inhibitor (AI) adherence and persistence were significantly influenced by out-of-pocket drug costs, dual eligibility status, and coverage gaps. Nonadherence to and nonpersistence with AET were associated with higher risks of all-cause mortality. Our findings of suboptimal AET adherence/persistence in Appalachia as well as positive associations between AET adherence/persistence and overall survival outcomes further underscore the importance of ensuring appropriate AET use in this population to reduce breast cancer mortality disparities. Our findings also suggest that intervention strategies focusing on individualized treatment and medication-related factors may improve adjuvant treatment use.